The Development of Islam and Democracy in Indonesia - Hamdan Zoelva (Constitutional Review, 2022)
Islam and democracy are two inseparable parts of social and political life in Indonesia. Textually, democracy itself does not exist in the Islamic Holy Qur’an or the Hadith (Prophet Muhammad’s words and actions). However, implicitly and substantially, the basics of democracy are in the teachings of Islam, both in the Qur’an and the Hadith. The principles of Islamic teachings, such as equality, deliberation, cooperation (ta’awun), and good habits (taghyir), are compatible with democratic values. In addition, many idioms that form the basis of ethics and morals in society are generally derived from the experience of the Prophet Muhammad, correlating with the basic principles of modern democracy. In the context of Indonesia, it is undeniable that Islam has contributed to the climate of democratization. This further confirms that Islam is not against democracy. Both support each other.